2015
DOI: 10.4236/ojg.2015.55033
|View full text |Cite
|
Sign up to set email alerts
|

Suggested Strategies in Water Treatment by Using Situ Pressure in Reverse Osmosis

Abstract: Nowadays desalination is one of the main resources to obtain water in many areas. The most advanced method for water filtration is reverse osmosis. In this system, water is injected into semimembranes by using power pumping, and its salt water is taken away from the solution. This paper has tried to offer guidelines to use the pressure created in situ of harvesting water, instead of utilizing power pump, which produces the necessary pressure for the reverse osmosis. These guidelines have been divided into 2 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Therefore, there is a ca. 53% increase in drinking water demand is projected by 2030 [1]. Other references reported that water demand will increase by 55% in 2050 [2].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is a ca. 53% increase in drinking water demand is projected by 2030 [1]. Other references reported that water demand will increase by 55% in 2050 [2].…”
Section: Introductionmentioning
confidence: 99%